4E cognition in the Lower Palaeolithic. (April 2021) - Wynn, Thomas; Overmann, Karenleigh A; Malafouris, Lambros
This essay introduces a special issue focused on 4E cognition (cognition as embodied, embedded, enactive, and extended) in the Lower Palaeolithic. In it, we review the typological and representational cognitive approaches that have dominated the past 50 years of paleoanthropology. These have assumed that all representations and computations take place only inside the head, which implies that the archaeological record can only be an "external" product or the behavioral trace of "internal" representational and computational processes. In comparison, the 4E approach helps us to overcome this dualist representational logic, allowing us to engage directly with the archaeological record as an integral part of the thinking process, and thus ground a more parsimonious cognitive archaeology. It also treats stone tools, the primary vestiges of hominin thinking, as active participants in mental life. The 4E approach offers a better grounding for understanding hominin technical expertise, a crucially important component of hominin cognitive evolution.